Perancangan Simulasi Supervisory Control and Data Acquisition pada Prototipe Sistem Listrik Redundant - Kurniawan, Muhammad Supono; Setiawan, Iwan; Triwiyatno, Aris (Departemen Teknik Elektro, Universitas Diponegoro, 2012)
The existence of electrical energy to human needs can not be separated, electrical energy is used by all humans on this planet from small scale region (household) to large-scale region such as industries. The electric energy quantity and quality demand of the electricity transmission system has been increasing over the time. Failure in the electricity transmission system can be fatal to the electrical components or operational loss in an industry. SCADA is proposed to accommodate these problems. It capables to monitor and control the disturbance on the electrical redundant system. The purpose of this final project is to simulate the SCADA on redundant power system to eliminate the failure of power transmission lines such as open-circuit failure, short circuit, and overload that can be controlled directly from the plant or through a computer interface. The Finite State Machine (FSM) and ladder diagram programming language are used to design the PLC system. There are hardware and software to support this final project, such as plant of redundant electrical systems, PLC CPM1A Omron, Laptop, CX One 9.0 software for programming the PLC and the CX Supervisor 3.0 to build the HMI. The result showed that the current sensors can be used to detect overload failure and simulate short circuit failure. Plant redundant electrical system can be monitored and controlled through the input-output of the plant, the interface on the computer, and World Wide Web. There is a relay on plant that can connect power lines to cutting power lines when the failure occurs. If an failure occurs in the form of open circuit, short circuit or overload the alarm and failure indicator will active. Keyword : SCADA, PLC, open circuit, short circuit, overload